2022
DOI: 10.1136/bmjopen-2021-058862
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal perceived capacity in life and physical punishment of teenage children: a longitudinal analysis of a population-based cohort in Tokyo, Japan

Abstract: ObjectivesPerceived capacity denotes a subjective sense of having resources to cope with strains and hardships, and hence maternal perceived capacity may be protective against risk factors for child maltreatment. This study investigated the longitudinal association between maternal perceived capacity in life and child maltreatment.DesignThis population-based longitudinal study used self-reported questionnaires from the Tokyo Teen Cohort study (TTC), a large community-based cohort study conducted in Japan betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In addition, literature [15] used logistic regression analysis as well as the chi-square test to quantitatively analyze the data on Dutch parents' disciplinary and rewarding educational styles for children, and the results showed that parents' combination of educational discipline and educational rewards in the educational process could help children better distinguish right from wrong and promote the progress of the parent-child relationship. Literature [16] analyzed the relationship between mothers' perceptual ability and adolescents' corporal punishment education with a research sample of 2515 mothers in Japan and East and West. The results showed that mothers' life perception ability can recognize adolescent corporal punishment education and can better help adolescents get out of the haze caused by educational discipline and rebuild confidence in learning and life.…”
Section: Review Of Relevant Studies On the Development Of Educational...mentioning
confidence: 99%
“…In addition, literature [15] used logistic regression analysis as well as the chi-square test to quantitatively analyze the data on Dutch parents' disciplinary and rewarding educational styles for children, and the results showed that parents' combination of educational discipline and educational rewards in the educational process could help children better distinguish right from wrong and promote the progress of the parent-child relationship. Literature [16] analyzed the relationship between mothers' perceptual ability and adolescents' corporal punishment education with a research sample of 2515 mothers in Japan and East and West. The results showed that mothers' life perception ability can recognize adolescent corporal punishment education and can better help adolescents get out of the haze caused by educational discipline and rebuild confidence in learning and life.…”
Section: Review Of Relevant Studies On the Development Of Educational...mentioning
confidence: 99%